Automatic Watering Monitoring System Using Solar Panel Resources at Agrapana Mushroom House Singosari District Malang Regency - Wardhana, Yoga Wishnu; Farida Arinie Soelistianto; Hariyadi, Aad; Mustafa, Lis Diana; Junus, Mochammad (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Ear fungus (Auricularia spp.) is a cultivated mushroom widely grown in controlled environments using substrates such as sawdust or agricultural waste. Maintaining optimal humidity and temperature is essential to ensure efficient growth and high productivity. This study proposes the design and implementation of an Internet of Things (IoT)–based automatic watering system integrated with a Peltier cooling module powered by solar energy to support environmentally friendly cultivation. The system utilizes a soil moisture sensor to monitor the humidity level of the planting medium and automatically activates a water pump through a relay module when watering is required. Environmental data are processed in real time to maintain stable growing conditions, reducing dependence on manual monitoring. Additionally, the system provides SMS notifications to inform cultivators of watering activities, enabling effective supervision and timely intervention. The proposed solution aims to simplify environmental control, improve watering accuracy, and enhance cultivation efficiency. The results indicate that the IoT-based automatic watering system can optimize humidity regulation, accelerate mushroom growth, and reduce labor requirements, making it suitable for ear fungus farming applications.